Pembahasan Kaidah Fikih Khusus dalam Ibadah Mahdah Berdasarkan Prinsip Tauqif dan Niat - Noor Halimah; Nabila Anggraini; Indra Hassbullah; Khairin Hafijhin; Lisnawati Lisnawati; M. Luthfi Setiarno (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
Mahdah worship holds a central position in Islamic teachings as a pure form of servitude to Allah SWT. Due to its tauqifi nature, the implementation of mahdah worship must strictly adhere to the provisions of the Sharia without additions or modifications. This study aims to examine and analyze specific fiqh principles that serve as guidelines in the practice of mahdah worship. A qualitative method with a library research approach was employed, through an in-depth review of classical and contemporary literature related to fiqh principles. The findings indicate that principles such as "the default rule in worship is tauqifi," "purity is not limited by time," and "no analogy (qiyas) applies to acts of worship whose rationale is unknown" function to safeguard the authenticity of worship practices from deviation. Understanding these principles is crucial to prevent innovations (bid‘ah) and to ensure that every act of worship remains aligned with Sharia directives. Furthermore, mastery of these principles assists muftis and jurists in issuing consistent and coherent fatwas. The implications of this study highlight the significance of fiqh education in strengthening the community’s awareness of authentic worship and providing a solid framework for evaluating religious practices amidst contemporary socio-religious dynamics.